Pengaruh Pengetahuan Produk, Labelisasi Halal, dan Cita Rasa Terhadap Keputusan Pembelian Street Food Lowokwaru Kota Malang - Salwa Auliya; Nur Hidayati; Mohamad Bastomi (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This research aims to analyze the influence of product knowledge, halal labeling, and taste on purchasing decisions among street food consumers in Lowokwaru District, Malang City. This research employed a quantitative approach with data collected through questionnaires distributed to 102 respondents selected using purposive sampling. The data were analyzed using multiple linear regression to assess the impact of each independent variable on the dependent variable. The results indicate that knowing a lot about a product doesn't greatly influence someone's choice to buy it. In contrast, halal labeling and taste have a positive and significant effect on people's choices when buying food. These findings indicate that street food consumers in Lowokwaru District place greater emphasis on halal aspects and taste rather than their level of product knowledge when making purchasing decisions. This study provides implications for street food business actors to pay more attention to halal certification and maintain taste quality in order to increase consumer purchasing decisions. Keywords: product knowledge, halal labeling, taste, purchasing decisions, street food